Endometriosis presenting as a rectal stricture in a patient with ulcerative colitis and primary sclerosing cholangitis: a case report - Chorley, Daniel; Mian, Ibrahim; Subhaharan, Deloshaan; Kakkadasam Ramaswamy, Pradeep (Frontiers in Gastroenterology, 2025)
Patients with ulcerative colitis (UC) are at an increased risk of colorectal cancer (CRC), which is compounded in the presence of other risk factors such as primary sclerosing cholangitis (PSC) and stricture. We report a middle-aged lady who developed a rectal stricture on the background of ulcerative colitis and primary sclerosing cholangitis. Although initial endoscopic biopsies showed no dysplasia, the patient proceeded with a total colectomy due to the concern for an underlying malignancy. Histology of the rectal specimens revealed endometriosis at the site of the stricture. This case emphasises the importance of evaluating the risk factor profile for malignancy in patients with ulcerative colitis while also highlighting the need to consider alternative aetiologies for rectal strictures.